Traditional and modern plasters for built heritage - Ranesi, Alessandra (2022)
Plasters have covered wide surface areas of buildings since antiquity, with a main purpose of indoor protection of the substrate on which they are applied. When no longer functional, they might require substitution with solutions that can combine compatibility with the substrate with the current need to mitigate building emissions. Indeed, plasters can contribute to lowering buildings’ energy demands while improving indoor air quality and the comfort of buildings’ users, as plasters can be used as passive regulators of relative humidity (RH). Hence, this study presents the relative-humidity-dependent properties of different plastering mortars based on clay, air lime, and natural hydraulic lime, and plastering finishing pastes based on gypsum and gypsum–air lime, in all cases tested using small size specimens. A cement-based plaster is also analysed for comparison. The clay-based plaster was the most promising material for RH passive regulation, and could be applied to repair and replace plasters in different types of buildings. Pastes based on air lime–gypsum could be applied as finishing layers, specifically on traditional porous walls. The sorption behaviour of cement plaster appeared interesting; however, its water vapour permeability was as expected, found to be the lowest, discouraging its application on historic walls.